Senegal : Sixth Review Under the Policy Support Instrument-Press Release; Staff Report; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report ;, 2018)
Growth remained strong at 7.2 percent in 2017, with inflation contained at 1.3 percent. Higher oil prices and increased capital goods imports significantly widened the current account deficit. The macroeconomic framework in this staff report uses a new GDP series which updates the base year from 1999 to 2014 and is approximately 30 percent higher in nominal terms relative to the previously reported GDP data series.